2020
DOI: 10.21597/jist.719099
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the Coat Protein Genome of Alfalfa Mosaic Virus (AMV) Isolates from Alfalfa in Van Province

Abstract: Van ilinde yetiştiriciliği yapılan yonca (Medicago sativa L.) bitkilerinde 2019 yılında virüslerin oluşturduğu simptomlara benzer belirtiler görülmüştür. Gözlenen belirtiler arasında cüceleşme, yapraklarda mozaik deseni ve sararma, rozetlenme ve küçük yaprak oluşumu yer almaktadır. Simptom gösteren ve göstermeyen bitkilerden toplanan 19 yonca yaprak örneğine, virüs genomunu tespit edebilmek için uygun primer çiftleri ile RT-PCR testi uygulanmıştır. Yonca yaprağı örneklerinden şiddetli belirtiye sahip altısı be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
(60 reference statements)
1
5
0
1
Order By: Relevance
“…isolates. This result is in agreement with the findings reported by various researchers using the same primer set in alfalfa and other plant species (Al-Saleh and Amer, 2013; Abdalla et al, 2019;Usta and Güller, 2020). Different primers can also be used in the diagnosis of AMV.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…isolates. This result is in agreement with the findings reported by various researchers using the same primer set in alfalfa and other plant species (Al-Saleh and Amer, 2013; Abdalla et al, 2019;Usta and Güller, 2020). Different primers can also be used in the diagnosis of AMV.…”
Section: Resultssupporting
confidence: 92%
“…The homology of CP gene sequences of both AMV isolates ranged from 97 to 99.37% with that of other members of the Alfamovirus genus. The phylogenetic interrelationship created from 21 CP sequences of AMV using the Neighbor-Joining algorithm indicated that both AMV sequences are closely related to alfalfa isolates from Van province (MT210179 and MT210178) and Iğdır province of Turkey (MW882262 and MW882261) ( Earlier literature suggested that AMV has existed for forty years in Turkey and various crops are highly susceptible to this infection (Erdiller and Lesemann, 1985;Çalı, 1990;Yardımcı and Açıkgöz, 1997;Çıtır, 1982;Usta and Güller, 2020). The presence of AMV has been reported in agroeconomic crops and weed such as potato, eggplant, Datura stramonium, bean, alfalfa, husk tomato, and pepper from agricultural region nationwide (Özdemir and Erilmez, 2007;Sertkaya et al, 2017;Ozdemir et al, 2011;Çulal Kılıç and Yardımcı, 2015;Çetinkıran and Baloğlu, 2011;Topkaya, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…AMV-infected pepper plants were reported in Samsun by Arli-Sökmen et al (2005), in Adana by Çetinkıran and Baloğlu (2011), and in Kahramanmaraş by Demir (2005). In addition, the presence of AMV in Türkiye was molecularly shown with RT-PCR in parsley in Konya , potato in Tokat (Topkaya, 2022), and alfalfa in Bingöl and Van (Usta and Güller, 2020;Güller et al, 2022). AMV was also reported in the provinces of Manisa, Balıkesir, and Burdur from different plant origins Kılıç and Yardımcı, 2015).…”
Section: Discussion Discussion Discussionmentioning
confidence: 94%
“…AMV has been detected in many plant species worldwide, not just in one region. It has been found in vegetable and forage crops, including alfalfa in Saudi Arabia (Al-Shahwan, 2002), soybean in China (Che et al, 2020), pea in Iran (Esfandiari et al, 2005), natural tobacco, alfalfa and pepper plants in Türkiye (Arli-Sökmen et al, 2005;Erdem, 2010;Usta et al, 2020;), potatoes in Canada (Xu and Nie, 2006), tomatoes in Lithuania (Zitikaitė and Samuitienė, 2008), and in many other studies. AMV is infectious to weeds, spice and ornamental plants, and various fruit trees; it has been detected in basil in Egypt, ornamental plants (Narcissus) and Campsis radicans known as trumpet creeper in Iran, Lavandula × Intermedia in Croatia, eggplant in Egypt, and medicinal plants (Gynostemma pentaphyllum) in China (Vrandečić et al, 2013;Pourrahim and Farzadfar, 2015;Al-Shahwan et al, 2017;El-Attar et al, 2019;Song et al, 2019).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 98%
“…Ülkemizde de yonca mozaik virüsü başta yoncalarda olmak üzere farklı kültür bitkilerinde rapor edilmiştir [12,[35][36][37][38][39][40][41].…”
Section: Virüslerden Kaynaklanan Zararın En Alt Düzeye Indirilebilmes...unclassified